Micromorphological and ultramicroscopic aspects of buried remains: Time-dependent markers of decomposition and permanence in soil in experimental burial. (June 2016) - Zangarini, Sara; Trombino, Luca; Cattaneo, Cristina
Highlights: New outlooks on post-mortem bone changes related to delimited decomposition stages. Metal oxides concentrations identified in bone tissue as violet-blue colorations. Sulphur percentages and Mg3 (PO4 )2 crystallizations in bones due to decomposition. Decrease in bone tissue phosphorus content with increasing PBI. The number of mineral grains observed in bone tissue grows up with increasing PBI. Abstract: A buried body not only determines an environmental response at the deposition site but it is also affected by the soil. The experiment was performed using eleven swine carcasses buried in an open site (Northern Italy). Changes occurring in bone tissue at different post-burial intervals were evaluated observing thin sections of bones through micromorphological and ultramicroscopic (SEM-EDS) techniques. These methods allowed the identification of: (a) magnesium phosphate (Mg3 (PO4 )2 ) crystallizations, probably linked to decomposition of bones and soft tissues; (b) significant sulphur levels which seem to be related to hydrogen sulphide (H2 S) fixation in bone tissue; (c) metal oxide concentrations in the form of unusual violet-blue colorations, which probably are evidence of the soil's action and penetration in bones, also testified by (d) the presence of mineral grains enclosed in the osseous tissue. The results underline the possibility of identifying both time-dependent markers of decomposition and indicators of permanence in soil in buried bones.